2017
DOI: 10.1155/2017/5984014
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Approach for the Formulation and Optimization of Solid Lipid Nanoparticles of Efavirenz by High Pressure Homogenization Using Design of Experiments for Brain Targeting and Enhanced Bioavailability

Abstract: The nonnucleoside reverse transcriptase inhibitors, used for the treatment of HIV infections, are reported to have low bioavailability pertaining to high first-pass metabolism, high protein binding, and enzymatic metabolism. They also show low permeability across blood brain barrier. The CNS is reported to be the most important HIV reservoir site. In the present study, solid lipid nanoparticles of efavirenz were prepared with the objective of providing increased permeability and protection of drug due to bioco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(86 citation statements)
references
References 49 publications
0
79
1
Order By: Relevance
“…Homogenization or ultrasonic technique is a simple method for producing nanoparticles in large-scale without the need for organic solvents and complex equipment [11]. In this study, a Magnetic Stirrer (Magnetic Heater) was used instead of a high shear homogenizer to prevent metal contamination and to increase PDI [34,35]. This method is a suitable structural model for encapsulating lipophilic drugs such as Rifampicin in SLNs regarding purposes for which it needs to be protected from deactivation and therefore it can be released slowly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Homogenization or ultrasonic technique is a simple method for producing nanoparticles in large-scale without the need for organic solvents and complex equipment [11]. In this study, a Magnetic Stirrer (Magnetic Heater) was used instead of a high shear homogenizer to prevent metal contamination and to increase PDI [34,35]. This method is a suitable structural model for encapsulating lipophilic drugs such as Rifampicin in SLNs regarding purposes for which it needs to be protected from deactivation and therefore it can be released slowly.…”
Section: Methodsmentioning
confidence: 99%
“…Stearic acid is a fatty acid (molecular weighing 284.48) with a medium-chain and negative charge at neutral pH, compared to the characteristics of any solid lipid, it is clear that stearic acid is the best choice for Rifampicin due to its good solubility in this lipid and the higher drug-loading potential [21,[35][36][37][38]. In the optimal formulation, 2% of stearic acid was used that particle size was between 300 and 400 nm, but in the formulation of more than 2.5%, particle size was reached to more than 500 nm.…”
Section: Size Pdi and Zpmentioning
confidence: 99%
“…A suspension with good colloidal stability (ζ > + 20 mV or < −20 mV) should not show aggregation, as a result of mutual electrostatic repulsion between the particles. 124 In addition, a modification process on QDs' surface (e.g., ligand addition) could be also evaluated using zeta potential analysis. 123 Ipe et al 125 reported the use of DLS and zeta potential techniques to confirm the protein cytochrome P450 BSβ conjugation with CdS and CdSe QDs.…”
Section: Dynamic Light Scattering and Zeta Potentialmentioning
confidence: 99%
“…1 In addition, the scaling up of the formulation technique to industrial production level is feasible at low cost and in a relatively simple way. 2 Gliclazide is an oral hypoglycemic useful for the treatment of non-insulin-dependent diabetes mellitus. Gliclazide exhibits slow GI absorption rate and wide inter individual variations in absorption and bioavailability.…”
Section: Introductionmentioning
confidence: 99%